Inhibition of fibronectin deposition improves experimental liver fibrosis - Altrock, Eva; Sens-Albert, Carla; Vasel, Matthäus; Dooley, Steven; Nakchbandi, Inaam (Journal of hepatology, 2015)
Common pathogenic steps in liver fibrosis are inflammation and accumulation of extracellular matrix proteins including collagen, which lead to disruption of tissue microarchitecture and liver dysfunction. Adequate fibronectin fibril formation is required for collagen matrix deposition in several cell types in vitro. We therefore hypothesized that preventing fibronectin fibril assembly will result in decreased collagen matrix accumulation, and hence diminish liver injury associated with fibrosis. In vitro studies on hepatic stellate cells and in vivo studies in mice were performed. In vitro studies on hepatic stellate cells confirmed that a fibronectin assembly inhibitor, pUR4 diminishes the amount of both fibronectin and collagen, accumulating in the extracellular matrix, without affecting their production. Induction of fibrosis using CCl4 or DMN was therefore combined with pUR4-treatment. pUR4 normalized the amount of fibrotic tissue that accumulated with injury, and improved liver function. Specifically, pUR4-treatment decreased collagen accumulation, without changing its mRNA expression. Most interestingly, we did not detect any changes in Kupffer cell numbers (F4/80+) or α-smooth muscle actin expressing hepatic stellate cell numbers. Further, there was no impact on TGF-β or TNF-α. Thus, in line with the in vitro findings, decreased fibrosis is due to inhibition of matrix accumulation and not a direct effect on these cells. In summary, a peptide that blocks fibronectin deposition results in decreased collagen accumulation and improved liver function during liver fibrogenesis. Thus, fibronectin matrix modulation offers a therapeutic benefit in preclinical models of liver fibrosis.